Psychotherapy incorporating horses for adolescents with autism and persistent emotional dysregulation: assessing meaningful change through personal goal attainment - Jenny C. den Boer; Anouk Sijbring; Nanda Rommelse; Wouter G. Staal; Helen Klip (Child and Adolescent Psychiatry and Mental Health, 2026)
Abstract Background Adolescents with autism often face significant challenges, which can lead to emotional dysregulation (ED). For some, existing treatments are inadequate. This study examined whether Psychotherapy Incorporating Horses (PIH), using the Pegasus protocol, supports improvements in emotion regulation through goal attainment in adolescents with autism and persistent ED. Methods This study included 36 adolescents (aged 11–18) with autism and persistent ED. Participants received 15 weekly PIH sessions. Individualised goals were assesed using Goal Attainment Scaling (GAS; -3 to + 2) at baseline and sessions 6, 10, and 15. Combined average GAS (c-GAS) were calculated per participant. Changes over time were analysed using the Friedman test with Bonferroni-corrected post hoc comparisons. Clinically significant improvement was defined as c-GAS ≥ 0. Results Data from 32 adolescents were analysed (mean age 13.8 years; 56% female). Improvement was observed in 65.6% of adolescents per self-report, with similar mother ratings and even higher father ratings (78.3%). Overall, 81.3% attained at least one goal. The highest attainment rates were observed for goals related to anger regulation and social abilities. Friedman tests showed significant improvements in c-GAS scores over time for all informants ( p < .001). Post hoc analyses indicated that improvements from baseline were significant at all time points. Discussion This study is the first to evaluate the Pegasus protocol using GAS as an outcome measure, highlighting its value as an innovative, patient-centred tool for capturing individualised progress. The findings suggest that PIH can effectively support goal attainment and improve emotion regulation in adolescents with autism and treatment-resistant ED.